Incidence, Clinical Characteristics, and Predictors of Cardiovascular Immune-Related Adverse Events Associated with Immune Checkpoint Inhibitors. (28th March 2022) - Isawa, Tsuyoshi; Toi, Yukihiro; Sugawara, Shunichi; Taguri, Masataka; Toyoda, Shigeru
Abstract : This article evaluates the incidence, clinical characteristics, and predictors of cardiovascular immune-related adverse events (CV-irAEs), focusing on the feasibility of serial cardiac monitoring using a combination of B-type natriuretic peptide, cardiac troponin T, and electrocardiogram for the prediction of future symptomatic (grade ≥2) CV-irAEs Abstract: Background: Cardiovascular immune-related adverse events (CV–irAEs) associated with immune checkpoint inhibitors (ICIs) may have been underreported given that most previous reports were retrospective. We aimed to evaluate the incidence, clinical characteristics, and predictors of CV–irAEs and determine the feasibility of serial cardiac monitoring using a combination of B-type natriuretic peptide, cardiac troponin T, and electrocardiogram for the prediction of future symptomatic (grade ≥2) CV–irAEs. Materials and Methods: This was a prospective observational study that included 129 consecutive patients with non–small-cell lung cancer who received ICI monotherapy at a single center. Serial cardiac monitoring was performed during ICI monotherapy. Results: A total of 35 (27%) patients developed any grade ≥1 CV–irAEs with a median time of onset of 72 (interquartile range 44-216) days after ICI treatment initiation. Multivariate Fine–Gray regression analysis showed that prior acute coronary syndrome (adjusted hazard ratio [HR] 3.15 (95% [CI], 2.03-4.91), prior heart failure hospitalization (adjusted HR 1.65 [95% CI, 1.17-2.33]), and achievement of disease control (adjusted HR 1.91, [95% CI, 1.16-3.14]) were significantly associated with grade ≥1 CV–irAEs. Serial cardiac monitoring revealed that patients with preceding grade 1 CV–irAEs were associated with a significantly higher risk of onset of grade ≥2 CV–irAEs compared with those without preceding grade 1 CV–irAEs (HR: 6.17 [95% CI, 2.97-12.83]). Conclusion: CV–irAEs were more common than previously recognized and have several predictors. Moreover, serial cardiac monitoring may be feasible for the prediction of future grade ≥2 CV–irAEs. Abstract : Thisarticle evaluates the incidence, clinical characteristics, and predictors of cardiovascular immune-related adverse events (CV-irAEs), focusing on the feasibility of serial cardiac monitoring using a combination of B-type natriuretic peptide, cardiac troponin T, and electrocardiogram for the prediction of future symptomatic (grade ≥2) CV-irAEs.